Women volleyball anaerobic threshold profile according to match position - Figueira, A.; Lauro, F.; Monteiro, A. (2001)
Volleyball athletes physical fitness profile according to match position and anaerobic threshold was analyzed in this study in Brazilian top level volleyball players at preparatory training period. We evaluated 16 women players (22.01+5.23 years old) and 10.3+4.2 as years of practice, shared in setters(S), center (CT), forward (FA) and universal attackers(UA). Weight did not present significant differences among groups, as well adiposity. Height were higher (p<.05) for CA compared to UA and S. Metabolic response were determined (Quinton-QMC) showing similar values for V02max. Anaerobic threshold (AT-I and II) was determined through ventilatory profile (VE) and equivalent respiratory ratio. Correlation values also were addressed for: treadmill velocity-km/h(V) and BMI; V and V02max; HR and V02max.